Assessment of the effectiveness of training and orientation of interns by introduction of specialized female surgical clinic - Gupta, Rachna; Sharma, Anshuman; Pandey, Sourabh; Badole, Sonu; Solanki, Vipiendra; John, Shany (International Surgery Journal, 2019)
Background: There is requirement of specialized female surgical clinics nowadays, which should be addressed routinely in the surgical department. For management of surgical problems in female patients, multidisciplinary approach mainly general surgery, obstetrics and gynaecology, general medicine, paediatrics, dermatology and psychiatry is required. The main aim and objective of this study is to assess the effectiveness of training and orientation of interns by introduction of specialized female surgical clinic. Methods: Prospective educational interventional study was conducted. 60 sensitized interns were introduced and oriented in the specialized female surgical clinic. A total of 952 patients visiting the clinic were studied. Statistical analysis was done. Results: Feedback of interns with respect to female patients were taken and recorded. There was a significant improvement in the knowledge and skill of the participating interns. Most of the interns were willing to continue their duties to such a specialized clinic in future. Conclusions: It can be concluded that the interns sensitized and exposed to this innovative method of training have shown a positive approach to this new method of learning. Such fully functional specialized female surgical clinic is required in hospital, in which participation of interns is useful.